Operational procedures of Kansas feedyards - Koons, L.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Twenty-four Kansas feedyards with 432,000 head capacity participated in a survey on operation procedures. The survey covered five areas: processing, animal health, rations, facilities, and marketing. Methods differed most in processing and starter-ration ingredients.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Feedyards; Processings; Rations